2017
DOI: 10.18632/oncotarget.18016
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 in cancer progression and metastasis: A systematic review

Abstract: Metastasis is the leading cause of cancer-related death and directly associates with cancer progression, resistance to anticancer therapy, and poor patient survival. Current efforts focusing on the underlying molecular mechanisms of cancer metastasis attract a special attention to cancer researchers. The epithelial-mesenchymal transition is a complex of molecular program during embryogenesis, inflammation, tissue fibrosis, and cancer progression and metastasis. S100A4, an important member of S100 family protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 169 publications
(202 reference statements)
13
125
2
2
Order By: Relevance
“…In addition to markers specifically expressed by epithelial tumor cells, we also observed differential expression in markers associated with tumor microenvironment, such as S100A4, which was upregulated in CC H (x 10.82; p = 1.5e −4 ). S100A4 is a member of the S100 calcium‐binding protein family, also known as fibroblast‐specific protein (FSP1) . Of note, we confirmed previous data showing an upregulation of S100 proteins (A6 and A11) by MALDI imaging in CC H , predominantly in the stromal part of the tumor .…”
Section: Resultssupporting
confidence: 90%
“…In addition to markers specifically expressed by epithelial tumor cells, we also observed differential expression in markers associated with tumor microenvironment, such as S100A4, which was upregulated in CC H (x 10.82; p = 1.5e −4 ). S100A4 is a member of the S100 calcium‐binding protein family, also known as fibroblast‐specific protein (FSP1) . Of note, we confirmed previous data showing an upregulation of S100 proteins (A6 and A11) by MALDI imaging in CC H , predominantly in the stromal part of the tumor .…”
Section: Resultssupporting
confidence: 90%
“…Similar to Gal1 and Opn, overexpression of the S100A4 protein in dKO liver could have different roles at different stages of CLI in mutant mice. On one hand, S100A4 may confer protection and show anti-inflammatory activity in response to aberrations of lipid metabolism (48), but on the other hand, it may favor tumor progression and metastasis in different cancers (49), including HCC (50). Furthermore, overexpression of the Ntrk2 (TrkB) protein in hepatocytes of the young dKO mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also involved in a wide range of biological functions, such as fibrogenesis and particularly inflammation regulation [16,23,24]. Previous studies have shown that S100A4 stimulated the releasing of various cytokines and growth factors that favors the inflammation process [25]. On the other hand, inflammation state in tissues was tightly associated with the HFD-induced obesity and obesity-related metabolic syndromes [26,27].…”
Section: Introductionmentioning
confidence: 99%